Full-genome sequence of Thalassotalea euphylliae H1, isolated from a Montipora capitata coral located in Hawai’i - Summers, Stephen (2019)
The isolate of Thalassotalea euphylliae H1 was collected from the surface of a Montipora capitata coral. The genome was assembled using long reads from a Nanopore MinION sequencer for scaffolding and complemented with short-read MiSeq sequences. The genome was approximately 4.77 Mb long with 4,020 protein-coding genes, 92 tRNAs, and 22 rRNAs.